Scientific basis for the industrialization of traditionally used plants of the Rosaceae family - García-Oliveira, Paula (2018)
© 2020 Elsevier Ltd Plants have been traditionally used for the treatment of different types of illness, due to biomolecules with recognised benefits. Rosaceae family is used in traditional Galician medicine. The following plants Agrimonia eupatoria, Crataegus monogyna, Filipendula ulmaria, Geum urbanum, Potentilla erecta and Rosa canina are usually found in treatments. The aim of this study is to perform an ethnobotanical review about the bioactive compounds of these plants and their different bioactivities, both studied in vitro and in vivo. The nature of the bioactive compounds is varied, highlighting the presence of different phenolic compounds, such as phenolic acids, flavonoids or tannins. Understanding the beneficial effects of the administration of the whole plant or target tissues from A. eupatoria, C. monogyna, F. ulmaria, G. urbanum, P. erecta and R. canina as well as those from their individual compounds could lead to the development of new drugs based on the use of natural ingredients.